Case report: Multifocal chronic paracoccidioidomycosis in an adult (Colombia Medica, 2011)
Paracoccidioides brasiliensis is the ethiological agent of one of the most prevalent systemic mycosis in Latin America, where around ten-million individuals are affected. Brazil has the highest incidence but in Venezuela, Colombia, Ecuador, and Argentina cases have also been reported. We describe a 56-year-old male with a one year history of lip, oral mucosa, and lung lesions. Granulomas and multinucleated giant cells were observed in histopathological evaluation with haematoxilyn-eosin stain. Mycologic studies (KOH and Gomori Grocott stain) showed blastoconidias with multiple budding. Serologic tests for paracoccidioidine were reactive. A diagnosis of chronic multifocal paracoccidioidomycosis was made. Initially, amphotericin B 0.7 mg/kg per day was started for fifteen days and consecutively itraconazole (400 mg/day) was administered orally with improvement of skin and lung lesions; however, an important residual fibrosis was observed. The patient was lost to follow up. We highlight the importance of an early diagnosis and adequate treatment to decrease sequelae in patient quality of life.